KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN, CSR SEBAGAI VARIABEL MODERASI - Hardian, Ananda Putra; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of financial performance and firm size to the firm value with the corporate social responsibility as the moderating variable. Financial performance is one of the factors which can be seen by investors in order to determine the stock investment. The result of the research shows that: 1) profitability has significant influence to the firm values. 2) Leverage does not have any influence to the firm value.3) Liquidity does not have any influence to the firm value. 4) Firm size does not have any influence to the firm value. 5) Corporate social responsibility does not have any significant influence to the profitability to the firm value. 6) Corporate social responsibility does not have any significant impact on the influence of the leverage to the firm value. 7) Corporate social responsibility does not have any significant influence on the influence of the liquidity to the firm value. 8) Corporate social responsibility does not have any significant influence on the influence of the firm size to the firm value.Keywords: Financial Perfomance, Firm Size, Firm Value, Corporate Social Responsibility